Construction and Optimization of the Ecological Security Pattern of Pinglu Canal Economic Zone Based on the InVEST-Circuit Theory Model - Zhanhao Dang; Baoqing Hu; Chunlian Gao; Shaoqiang Wen; Jinrui Ren; Yunfei Liang (Land)
The strategic delineation of ecological corridors and establishment of robust ecological security frameworks constitute fundamental prerequisites for advancing ecologically balanced growth and premium development within the Pinglu Canal Economic Belt. In this study, a comprehensive framework integrating ecological sources, resistance surfaces, and ecological corridors was developed using the InVEST model combined with circuit theory. The framework was then applied to assess the spatial and temporal dynamics of four major ecosystem services over the period from 2000 to 2020. The main findings are as follows: (1) From 2000 to 2020, the values of the four ecosystem services showed an overall declining trend. Spatially, areas with high ecosystem service importance were mainly concentrated in woodland and grassland areas in the southwest and northwest of the region. (2) The resistance values of the study area’s resistance surface ranged from 1 to 4.83. High-resistance areas were primarily located in the central region, corresponding to areas of intense human activity, while low-resistance areas were distributed around the periphery and largely overlapped with ecological source areas, presenting a spatial pattern of “high in the center, low at the edges”. (3) In total, 119 ecological barriers, 28 corridors, 8 critical pinch points, and 16 habitat source areas were identified. Building on these results, an enhanced ecological security layout—defined by the ‘three belts and three zones’ strategy—was formulated to guide restoration efforts and inform ecological management across the Pinglu Canal Economic Region.